Identifying Gene Variants That Are Pathogenic In Osteoporosis Using An Omics Data And Bioinformatics Approach - Danang Prasetyaning Amukti; Lalu Muhammad Irham; Ria Indah Pratami; Wirawan Adikusuma (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Introduction. The biological cause of osteoporosis, a metabolic bone disease, is osteoclastic bone resorption that is not offset by osteoblastic bone synthesis. Fractures become more likely as a result of the bones being brittle and weak. Common genetic variants that indicate hereditary susceptibility factors to osteoporosis in the general population, as well as mutations affecting specific genes that cause uncommon monogenic causes of osteoporosis, are the two main types of osteoporosis. Bone defects can now be caused by numerous additional genes. In this study, we aimed to identify variants of this pathogen across continents using genome-based and bioinformatics methodologies. Methods. We integrated osteoporosis-associated variants into this study using various bioinformatics-based techniques by using GWAS data from the National Human Genome Research Institute (NHGRI). Results. We found that the variant rs3742909 is likely to cause osteoporosis. SMOC1 gene expression in whole blood tissue also appears to be affected by this variant. We found that this genomic variant requires additional research to validate functional and clinical studies in patients with osteoporosis. Conclusions. We suggest that better understanding of disease susceptibility, including osteoporosis, can be achieved through the merging of genome-based databases and bioinformatics. Our goal is to validate the findings of this study both in vitro and in vivo during the preclinical stage.